NATURAL-SIMULATION MODEL OF PHOTOVOLTAIC STATION GENERATION IN PROCESS OF ELECTRICITY BALANCING IN ELECTRICAL POWER SYSTEM - Lezhniuk, Petr; Komar, Viacheslav; Hunko, Iryna; Jarykbassov, Daniyar; Tussupzhanova, Dinara; Yeraliyeva, Bakhyt; Katayev, Nazbek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The paper analyzes the methods of stabilizing generation schedules of photovoltaic stations (PV) in electric power systems (EPS) in the process of balancing electricity. Since PV is characterized by the instability of electricity production due to dependence on weather conditions, an automatic system for forecasting their generation schedules (ASFG) for the next day has been created to increase the energy efficiency of PV. The process of automating the prediction of the power stations as part of the balancing group of the power stations and the algorithm for adjusting the prediction of power plant generation are considered. The criterion for managing the forecasting process is the minimization of the difference between the values ​ of forecasted and actual generation for the same period of time. Checking the performance and tuning of the ASFG PV in order to evaluate its functioning and the effectiveness of its application in the task of balancing the states of the EPS is possible only by means of simulation. It is shown that based on the nature of the process of forecasting the generation of PV using ASFG, it is advisable to use simulation modeling. Since the actual value of generation is constantly monitored during balancing using ASFG, it is possible to use these values ​​during simulation and proceed to real-time simulation. In this case, modeling is considered as an experimental method of research, according to which it is not the object itself that is subjected to perturbations and research, but the software-implemented computer model of the object. The real-life simulation model of the operation of the PV makes it possible to more fully consider the various modes of their operation in the process of balancing the modes of the EPS as part of the balancing group and to more reasonably choose decisions regarding the participation of the PV in generation, taking into account weather conditions and the limitations of the system operators of transmission and distribution of electricity.